BETWEEN TWO WORLDS: TIMOTHY MO'S SOUR SWEET - Setefanus Suprajitno (K@ta: A Biannual Publication on the Study of Language and Literature, 2002)
Timothy Mo is an Anglochinese writer who writes much about the experiences that immigrants face in their new country, and how they overcome the problems and culture shocks that come up, as well as how they define their identity. In his novel, Sour Sweet, Mo describes how three characters who come from Hong Kong, Chen, Lily, and Mui, with their all character traits live their lives in the United Kingdom. This paper discusses how the three characters respond to their new environment. Because of different character traits and ability to cope with changes, they respond to the culture and society of the UK differently. There is one who holds the old culture tightly without trying to understand the new culture in the new place, there is one who rejects the old culture and adapts the life in the UK in an uncritical manner, yet there is one who tries to find the equilibrium between the old and the new. By showing the flexibility towards the changes and the influence of foreign culture, Mo emphasizes in the need of accommodative attitude and tolerance towards the multicultural reality in this modern world.